2018
DOI: 10.21859/jech.5.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Regular Physical Activity among Employees of Healthcare Network: Application of Health Belief Model

Abstract: Background & Objective:Inactivity is one of the 10 leading causes of death in the world, doubling the risk of cardiovascular disease. Health belief model (HBM) is an effective model in predict the regular physical activity behavior. This study aimed at identifying determinants of the regular physical activity in order to prevent cardiovascular diseases, using HBM. Instruments & Methods:This descriptive-analytical cross sectional study was conducted on employees working in a healthcare network affiliated to Ila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The study revealed that, among HBM constructs, the perceived severity of CVD was found to be significantly associated with the likelihood of bank workers engaging in CVD preventive behaviors. A similar result was reported from Rahmati-Najarkolaei et al’s study on students’ likelihood to engage in CVD preventive behaviors [ 31 ], a study by Jorvand et al regarding healthcare workers’ CVD preventive behaviors [ 32 ], and Oruganti et al’s study on measuring the health beliefs of hypertensive patients [ 33 ]. This indicates that respondents’ belief about the severity of CVD is a key to improving their perception of CVD preventive behaviors.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The study revealed that, among HBM constructs, the perceived severity of CVD was found to be significantly associated with the likelihood of bank workers engaging in CVD preventive behaviors. A similar result was reported from Rahmati-Najarkolaei et al’s study on students’ likelihood to engage in CVD preventive behaviors [ 31 ], a study by Jorvand et al regarding healthcare workers’ CVD preventive behaviors [ 32 ], and Oruganti et al’s study on measuring the health beliefs of hypertensive patients [ 33 ]. This indicates that respondents’ belief about the severity of CVD is a key to improving their perception of CVD preventive behaviors.…”
Section: Discussionsupporting
confidence: 81%
“…Findings of the study revealed that perceived self-efficacy is not significantly associated with bank workers’ perception of CVD preventive behaviors. However, a study conducted by Sharifzadeh et al in Iran [ 29 ], Sabzmakan et al’s study [ 36 ], Baghianimoghadam et al’s study [ 21 ], Rahmati-Najarkolaei et al’s study among Tehran University students [ 31 ], Mohammadi et al’s study among school females [ 35 ], Jordan et al’s study [ 32 ], and with a study done by Kahnooji et al [ 34 ] regarding CVD preventive behavior. This outlines that in various studies perceived confidence is an important factor in improving their probability of adopting health behaviors though it is not statistically significant in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous studies have also confirmed the benefits of regular physical activity as another important factor affecting health, since a sedentary lifestyle is associated with the risk of many chronic diseases; every year, about two million deaths are reported worldwide due to adopting a sedentary lifestyle [ 17 ]. Different studies have reported that awareness, perceived severity, and self-efficacy are the main variables predicting women’s physical activity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Iran have also shown that teachers' lifestyle is not healthy, especially in the field of physical activity, as Pirzadeh's study showed that only 24% of teachers had a sufficient level of physical activity (Pirzadeh et al, 2012). Regular physical activity is a complex behavior that is difficult to change and maintain and is influenced by a variety of individual factors, including demographic and cognitive variables (Jorvand, Tavousi, & Ghofranipour, 2018). Other factors that determine the level of physical activity in adulthood include environmental, social, economic, physical, and cultural factors (Tojari, A, Ilbeigi Asl, & Rezaean, 2011).…”
Section: Introductionmentioning
confidence: 99%